2014
DOI: 10.1111/etho.12063
|View full text |Cite
|
Sign up to set email alerts
|

Narcotics Anonymous: Anonymity, Admiration, and Prestige in an Egalitarian Community

Abstract: Narcotics Anonymous (NA) supports long‐term recovery for those addicted to drugs. Paralleling social dynamics in many small‐scale societies, NA exhibits tension between egalitarianism and prestige‐based hierarchy, a problem exacerbated by the addict's personality as characterized by NA's ethnopsychology. We explore how NA's central principle of anonymity normatively translates into egalitarianism among group members. Turning to the lived reality of membership, building on Carr's () concept of script flipping, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
0
6
1
Order By: Relevance
“…To build Connectedness and support recovery Abedi and colleagues [ 43 ] and the present study emphasize that ‘experienced’ NA members as well as ‘newcomers’ are important (i.e., ‘experienced’ peers provide hope that stable recovery is possible, ‘newcomers’ provide hope by sharing their initial recovery steps and also confront members with the negative effects of substance use). Interestingly, this finding is in sharp contrast with the study by Snyder and Fessler [ 59 ] who indicated that despite the egalitarian principles of NA serious status differences may emerge between more ‘experienced’ members and ‘newcomers’. These different findings might be explained by sampling differences (e.g., ‘enthusiasts’ in the present study) and potential barriers NA-members experience in raising difficulties they encounter in NA as put forward by Christensen [ 60 ].…”
Section: Discussioncontrasting
confidence: 91%
“…To build Connectedness and support recovery Abedi and colleagues [ 43 ] and the present study emphasize that ‘experienced’ NA members as well as ‘newcomers’ are important (i.e., ‘experienced’ peers provide hope that stable recovery is possible, ‘newcomers’ provide hope by sharing their initial recovery steps and also confront members with the negative effects of substance use). Interestingly, this finding is in sharp contrast with the study by Snyder and Fessler [ 59 ] who indicated that despite the egalitarian principles of NA serious status differences may emerge between more ‘experienced’ members and ‘newcomers’. These different findings might be explained by sampling differences (e.g., ‘enthusiasts’ in the present study) and potential barriers NA-members experience in raising difficulties they encounter in NA as put forward by Christensen [ 60 ].…”
Section: Discussioncontrasting
confidence: 91%
“…Normative standards for recovery and what it means to be a “good mother” are set in stone, often to the detriment of those they are meant to help (Kitty & Dej, 2012; Phoenix & Woollett, 1991). Singling out pregnant women in the addiction community may be evidence of an underlying hierarchy that exists within recovery programs, despite the professed concept that everyone working the 12-steps is equal (Snyder & Fessler, 2014). The efforts of peer mentors and other supportive organizations, and ultimately the health of the mother, may be undermined if systematic structural vulnerabilities are not addressed (Bourgois, Holmes, & Quesada, 2017; Bungay, 2013; Torchalla, Linden, Strehlau, Neilson, & Krausz, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…When I asked Yessica how she would balance her new responsibilities with her existing relationships, she replied in English, “Well, I guess we all gotta be bitches here!” Yessica's response reveals how difficult it can be to manage the competing directives of her two social roles. When she tried to exercise her authority, her friends accused her of being “bitchy” and continued talking, perhaps to re‐establish an egalitarian relationship (Snyder and Fessler 2014). She reported them, but Sara—busy with paperwork for new inpatients—told Yessica to handle it on her own.…”
Section: “I Guess We All Gotta Be Bitches Here!”: Blurred Social Role...mentioning
confidence: 99%
“…I focus on service workers, particularly inpatient-guards, to examine how the non-egalitarian role of the guard stands in tension with the assumption of equality Alas's director presumed in imagining therapeutic process through mutual aid. Just as Snyder and Fessler (2014) point out the prestige hierarchy embedded in 12 Step programs based on experience; the existence of the inpatient-guard position creates distinctions among inpatients based on their therapeutic progress. This hierarchy of inpatients can be seen in the therapeutic distribution of labor.…”
Section: Complicating Goffman's Total Institutions Through Social Rolesmentioning
confidence: 99%